A Study of At-Home and Out-of-Home Parental Involvement and Student Achievement in English / Liaw Shun Chone and Angelina Subrayan - Liaw, Shun Chone; Subrayan, Angelina (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2008)
This research discussed the strength of relationship between parental involvement and student achievement. Parental involvement in children's learning at-home and out-of-home is considered crucial to the achievement in the English Language. This study includes both quantitative and qualitative research. The quantitative study consists of a sample of 160 students from 4 different schools in an urban town. The researchers administered questionnaires to students to investigate the significant relationship between parental involvement and student achievement. The quantitative study found that parental involvement at-home and out-of-home correlated positively with varying degree to student achievement in the Penilaian Menengah Rendah (PMR) English Language. Generally, the findings from the interviews with parents in qualitative research reflected almost similar results obtained from the questionnaires administered to upper secondary students in quantitative research. Comparatively, the results of parents' intensity of involvement at home and out-of-home correlated with student achievement in PMR English examination.